Makanan Halal dan Thayyib bagi Kesehatan Siswa Perspektif Al-Qur’an di Madrasah Ibtidaiyah Terpadu Lailatul Qodar - Daryanto, Daryanto; Handayani, Rina Tri; Tobroni, Imam; Abidin, Sahal; Fatimah, Amalia Nurul; Aminudin, Muhamad Fauzan (Kartika: Jurnal Studi Keislaman, 2025)
This qualitative study, using a case study method, aims to explore the application of the principles of halal and thayyib foods from QS. Al-Baqarah: 168 regarding students' health at MI Terpadu Lailatul Qodar. Using observation and in-depth interviews, the study focused on the consumption patterns and perceptions held by teachers and students and curricular and extracurricular elements of nutrition literacy, incorporating Qur'anic teachings at MI Terpadu Lailatul Qodar. The results showed that the school gave students halal-thayyib snacks and lunches and had rules against bringing pocket money, which helped stop the everyday unhealthy snacking habits at that age. Teachers think that Thayyib includes nutrition, hygiene, health, and the spiritual side of academics. Students can show that they understand unhealthy food and its risks based on their experiences when there is less formality. Life skills classes like Cooking and Market Day help reinforce these values even more. In fact, problems come from parents who give their kids money and kids who like tasty snacks. This study concludes that while the holistic integration of religious values is effective, strong synergy between the school and family is critical for lasting behavioral change.